The risk to structures built near roads and rails used for moving hazardous materials - Vaidogas, Egidijus Rytas; Kisežauskienė, Lina; Girnienė, Ingrida (Journal of Civil Engineering and Management, 2016)
An assessment of parts of transportation infrastructure in terms of hazards to roadside territory is considered. It is suggested to assess individual segments of road and railway network by estimating risks posed by potential fires and explosions on road and rail. Boiling liquid expanding vapour explosion of tanker trucks and tank cars is identified as the most hazardous and likely high consequence accident in the land transport. It is proposed to express the risk to built roadside objects by means of an annual damage frequency. This frequency is considered to be a specific physical characteristic of the road or railway segment under analysis. It is shown that estimating the damage frequency requires assessing effects of a potential explosion on road or rail and developing a fragility function for the roadside object analysed as a potential target. An example case study is presented. It considers a potential thermal damage to a reservoir (stationary tank) built in the vicinity of a highway. The damage can be caused by an explosion of a propane tanker truck. Results of the risk assessment are expressed in terms of probabilities of specific damage events.